2018
DOI: 10.1080/15388220.2018.1488136
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Bullying Involvement in Adolescence: The Role of Gender, Age, and Mental Health

Abstract: We analyzed the associations between sexual orientation and subjection to/ perpetration of bullying at school, taking into account confounding by psychiatric symptom dimensions and involvement in the other role. Survey data among 25,147 boys and 25,257 girls in comprehensive school, and 33,231 boys and 36,765 girls in upper secondary education in Finland were used. Data were analyzed using cross-tabulations with Chi-square statistics and logistic regression. Even though associations between sexual minority sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Given that from early to late adolescence, both cognitive abilities including perspective taking, emotional and behavioral controls and sexuality mature (Cacciatore et al., 2018 (under review); Moshman, 2011 ; Steinberg, 2005 ) it could have been expected that in peer groups of middle to late adolescents, sexual harassment behavior would decrease and the adolescents would be more careful not to directly or indirectly infringe the boundaries of their potentially more vulnerable peers, such as those belonging to sexual minorities. As to school bullying, such favorable development has been suggested (Kurki-Kangas et al., 2018 ). The same aspects of progressing development could also make sexual minority adolescents themselves more able to cope with minority stress and therefore less vigilant for heterosexist communications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that from early to late adolescence, both cognitive abilities including perspective taking, emotional and behavioral controls and sexuality mature (Cacciatore et al., 2018 (under review); Moshman, 2011 ; Steinberg, 2005 ) it could have been expected that in peer groups of middle to late adolescents, sexual harassment behavior would decrease and the adolescents would be more careful not to directly or indirectly infringe the boundaries of their potentially more vulnerable peers, such as those belonging to sexual minorities. As to school bullying, such favorable development has been suggested (Kurki-Kangas et al., 2018 ). The same aspects of progressing development could also make sexual minority adolescents themselves more able to cope with minority stress and therefore less vigilant for heterosexist communications.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents of different ages likely perceive social interactions differently, and therefore the associations between sexual minority status and conceptions of experiencing sexual harrassment may differ between adolescents of different ages. It has, for example, earlier been shown that involvement in school bullying decreased with age both among heterosexual and sexual minority youths (Kurki-Kangas, Marttunen, Fröjd, & Kaltiala-Heino, 2018 ). Similar development could be expected regarding sexual harassment.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the theory of heteronormativity and heterosexism, sexual minority (Alanko, 2014; Kaltiala‐Heino et al, 2019) and gender minority (Alanko, 2014; Mitchell et al, 2014; Toomey et al, 2012; Ybarra et al, 2015) adolescents appear to suffer from sexual harassment more commonly than those belonging to cisgender, the heterosexual majority. Sexual minority (Kurki‐Kangas et al, 2019; Ybarra et al, 2015) and gender minority (Ybarra et al, 2015) youth have also been found to report disproportionately frequent experiences of bullying, a considerable share of which is of a sexual nature (Ashbaug & Cornell, 2008) and may indirectly relate to gender and sexuality even when explicitly having unrelated content (Alanko, 2014; Lehtonen, 2003). A Spanish study reported that among transgender people, those disclosing their gender identity during adolescence experienced more harassment related to gender expression and sexuality than did those disclosing their gender identity only later (Devis‐Devis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lesbian, Gay and Bisexual (LGB) adolescents in Iceland were more likely to bully others than non-LGB students (Thorsteinsson et al, 2017). In a Finnish study (Kurki-Kangas et al, 2019), same-and both-gender sexual minority youth were more likely to bully others than their exclusively opposite-gender attracted peers. Other findings report that bisexual girls are more likely to have been bullies-and victims-than heterosexual girls (Berlan, Corliss, Field, Goodman, & Austin, 2010).…”
Section: Introductionmentioning
confidence: 99%